THE RELATIONSHIP BETWEEN BODY MASS INDEX (BMI) AND HYPERTENSION ON ELDERLY IN MUHAMMADIYAH REGIONAL LEADERS OFFICE (PDM) OF SLEMAN - Ega Via Ambarwati; Indriani; Agus Riyanto (JURNAL KESMAS DAN GIZI (JKG), 2023)
Abstract Background: Hypertension is a non-communicable disease (NCD) which is the main cause of death globally. The prevalence of hypertension continues to increase and is often known as "The Silent Killer". The obesity factor (BMI>25) is also one of the causes of hypertension. Objective: The aim of this study is to assess the correlation between Body Mass Index (BMI) and the incidence of hypertension in the elderly population living in the Muhammadiyah Regional Leadership (PDM) Sleman area. Method:This research is an observational analysis with a cross-sectional approach. The sample consisted of 110 people using purposive sampling. The instruments used include digital scales, microtoise staturemeter and digital sphygmomanometer. Data analysis using univariate and bivariate analysis methods using the Chi Square correlation test. Results : The results of the analysis show that the majority of respondents have characteristics, namely: 49.1% aged 45-59 years, 86.4% are women, 45.5% have secondary education, 51.8% work as housewives, 50.0% experience obese and 82.7% suffered from grade I hypertension. A significant correlation between BMI and blood pressure was identified (P<0.001). Conclusion:A significant correlation was detected between BMI and blood pressure with increasing BMI associated with increasing blood pressure in the elderly. Suggestion: Can collaborate with relevant universities regarding health checks so that they can control the health of congregation members.   Key words : Body Mass Index (BMI), Hypertension